Analisis Motivasi Remaja Bergabung pada Komunitas Arung Jeram di Kabupaten Aceh Tengah - Diyo Setiawan; Novia Rozalini; Irfandi Irfandi (Jurnal Pustaka Cendekia Pendidikan, 2026)
Rafting has become more than a recreational sport, serving as a medium for character building, teamwork, and the development of adolescents’ physical and mental abilities. The growing participation of adolescents in rafting communities highlights the importance of understanding the factors that motivate their involvement. This study aimed to analyze the intrinsic motivation, extrinsic motivation, and obstacles experienced by adolescents in joining a white-water rafting community in Central Aceh Regency. A qualitative descriptive approach was employed involving 13 informants, consisting of six athletes, six non-athletes, and one coach from the Uning Rafting Community. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Intrinsic motivation included interest in water sports, the desire for new experiences and challenges, personal enjoyment, and self-development. Extrinsic motivation was influenced by peers, family support, coach encouragement, and opportunities to participate in competitions and achieve achievements. The main obstacles included weather and environmental conditions, physical limitations, and psychological barriers during training and competitions. Both intrinsic and extrinsic motivation play a significant role in encouraging adolescents to join and sustain their participation in the rafting community in Central Aceh Regency.